The Constitutionality of the TAP MPR’s Decisions in the Legislative Hierarchy - Brillian Gustama; Sholahuddin Al-Fatih (Journal of Morality and Legal Culture, 2022)
This study aims to analyze the influence of TAP MPR in Indonesia. Placement of MPR Provisions in Law No. 12 of 2011 on the hierarchy of Legislation in Indonesia becomes one of the problematics that needs to be discussed, on the grounds of the position of MPR provisions that are under exactly the Constitution of 1945. This is based on the position of the MPR Decree itself which will automatically become a reference to the rules under it, in accordance with the theory of stairs put forward by Hans Kelsen. Although from the point of view of the position of MPR determination is still understandable if Hans Nawiasky theory is used as the basis. But in terms of testing itself of course this will raise a big question mark for all of us because in the Constitution of 1945 institutions or institutions that have the right to conduct a test of the Law is the Constitutional Court and the Supreme Court, but within its own scope the Provision of MPR is outside the juridical territory of the two Institutions themselves. Therefore, there needs to be a solution if at any time the MPR Decree is not in accordance with the basis of the 1945 Constitution so that there will be no defects in one of the legal sources of the State of Indonesia.